Child survival: district hospitals and paediatricians. Issue 9 (19th August 2005) - English, M
Abstract : In a previous article in this series, Zulfiquar Bhutta outlined many of the key sociopolitical issues, both national and international, that currently affect the delivery of health care to children in developing countries. 1 The clear summary of our situation is that we are failing to provide even basic health care (both preventive and curative) that could reduce child mortality globally by more than half. 2 Paediatricians, who have perhaps in the past felt they were at the forefront of articulating and promoting a global health agenda, should be challenged by these conclusions. The successful ratification of the United Nations Convention on the Rights of the Child 3 that unequivocally target health was not a finishing line, a goal achieved, but rather a foundation for action. Therefore while researchers might have felt some satisfaction at successes in defining optimum treatment approaches, the pathways to delivering services were, and remain, far from clear. Progress is further complicated by the diverse conditions and obstacles that may be encountered worldwide.